Cell-based assays for evaluation of autophagy in cancers - Pang, Siew Wai *; Awi, Noel Jacques *; Yap, Hooi Yeen *; Teow, Sin Yeang * (InTechOpen, 2019)
Autophagy is a cellular mechanism that degrades damaged organelles and misfolded proteins to maintain cellular homeostasis. Autophagy in cancers is drawing increasing attentions due to its multifaceted roles in cancer development, progression, and treatment. There are several key autophagy effectors that are being extensively studied to understand the role of autophagy in cancer as well as their potential value as predictive and/or prognostic biomarkers and therapeutic target. These include ATG4A, ATG4B, Beclin-I, p62, LC3A, LC3B, LC3C, and LAMP. While having its own sophisticated pathway, autophagy has been reported to associate with multiple oncogenic pathways such as NF-kB, mTOR, and PI3K signaling. This chapter aims to provide a detailed protocol for researchers to investigate the role of autophagy using in vitro cell line as model. Here, we demonstrate several techniques including Western blot (WB), immunofluorescence (IF), and small-interfering RNA (siRNA) knockdown using colorectal cancer cell lines as samples. This chapter provides information to researchers especially those in their early- and mid-career to plan and design their experiments to study the autophagy events in their area of interests.